Aksetid, det aksiale, aksialisering. Om Robert Bellah & Hans Joas, eds., The Axial Ages and Its Consequences - Petersen, Anders Klostergaard (Religionsvidenskabeligt Tidsskrift, 2013)
ENGLISH ABSTRACT: The collective work The Axial Age and Its Consequences contains contributions by Charles Taylor, Merlin Donald, Shmuel N. Eisenstad, Jan Assmann and others to important discussions before, around and after Robert Bellah's Religion and Human Evolution. The article presents and discusses the indi-vidual contributions. DANSK RESUMÉ: I samleværket The Axial Age and Its Consequences er samlet bidrag af Charles Taylor, Merlin Donald, Shmuel N. Eisenstad, Jan Assmann og flere andre til vigtige debatter forud for, parallelt med og opfølgende på Robert Bellahs Religion and Human Evolution. Artiklen præseterer og diskuterer værkets bidrag.